Comparison of group-based and individually training in patients with diabetes mellitus: 2-year follow-up study (Annals of Medical Research, 2021)
None
Keywords: key, between March/2016 and March/2018. The HbA1c levels of 96 patients who were trained in a diabetes school and 99 patients who were individually trained in the outpatient clinic were measured. The treatments of the patients trained in the outpatient clinic had also recently been changed, either by the addition of a new medication (oral anti-diabetic drugs or insulin) and/or by increasing the dosages of their current medications.br /Results: The mean HbA1c level was 9.29±1.90 for the diabetes school patients and 9.73±1.22 for the individually trained group patients (p0.05). It was found that HbA1c regressed to 8.25±1.84 three months after the training in a school, while the regression was 8.34±1.66 in the outpatient trained group (p0.05). No difference was detected between groups in terms of lowering HbA1C. Group-based training provided a more efficient HbA1c decrease in male patients, who had a body mass index (BMI) of ≥30, and in those who received intensive insulin therapy. However, at the first year follow up, HbA1c showed a tendency to increase again in the diabetes school group.br /Conclusion: Group-based training is a cost-effective method that may also decrease anti-diabetic requirement and provides more patient satisfaction, along with higher patient compliance. However, for long-term success, the training should be continuous and should be held at least once a year to provide up-to-date information.br / Diabetes mellitus; group-based training; individual training; Hemoglobin A1c.